Feng Shui and it's application in town planning / Madzlan Jamaluddin - Jamaluddin, Madzlan (1994)
What is Feng Shui? There have been many definitions offered by writers who studied the subject of Feng Shui . Ernst Borsehmann wrote in his book Picturesque China that " Feng Shui means wind-water, but in its wider sense, stands for the relation to the surrounding nature, influence of the landscape on the beauty buildings and the happiness of the inhabitants". In practice, Feng Shui is something between a science and an art which Westerners often call Chinese Geomancy. Feng Shui is influenced by I-Ching or Book Of Changes, which is the mother of Chinese thoughts and practices. It stresses the connection between man's destiny and nature.